The use of information and communication technologies in the work of primary school teachers - Gorbunova G. A., Nikolaeva M. M. (Pedagogical experience: theory, methodology, practice, 2016)
children - are members of the Information Society. The amount of information that falls on them, many times the amount that comes to their peers even two decades ago. Information skills are already firmly part of their mentality: they cleverly managed with a variety of electronic devices, almost without reading the manuals and guides; all kinds of players, mobile phones have become an integral part of their equipment. It must be remembered and on the qualitative composition of information that may not always be a "raw material" for the formation of knowledge. Therefore, as the author notes, the main task of informatization of educational process in elementary school - is the management of information flow, which assumes the student, his hierarchization, structuring and combining.
Keywords: информация; информационно-коммуникативные технологии; информатизация; комбинирование; учитель начальных классов; information and communication technologies; information; structuring; информационный поток; иерархизация; структурирование; a combination; a primary school teacher; the flow of information; hierarchization